Konflik Agraria dan Perlindungan Masyarakat Adat: Analisis Hukum atas Pembangunan Berkelanjutan di Indonesia (Hakim: Jurnal Ilmu Hukum dan Sosial, 2026)
Agrarian conflicts in customary forest areas in Indonesia, particularly in Eastern Indonesia, have shown increasing intensity alongside the expansion of natural resource-based development. Although normative legal recognition of indigenous peoples has been established through various legal instruments, policy implementation remains inconsistent, leading to conflicts and legal uncertainty. This study aims to analyze the consistency of legal frameworks governing customary forests, identify patterns of agrarian conflict, and examine the gap between legal norms and their implementation within the framework of sustainable development. The research employs a normative legal approach strengthened by limited empirical analysis, utilizing statute, conceptual, and case approaches. Data were obtained from primary and secondary legal materials, as well as reports on agrarian conflicts in Papua and Maluku. The findings reveal regulatory fragmentation among agrarian, forestry, and sectoral policies, resulting in state dominance over forest areas and delays in the formal recognition of customary forests. Furthermore, agrarian conflicts are predominantly driven by investment expansion in forestry, plantation, and mining sectors, reflecting an imbalance in the implementation of sustainable development principles. The gap between das sollen and das sein emerges as a key factor hindering effective legal protection for indigenous communities. This study contributes to the development of critical legal perspectives on sustainable development and provides policy recommendations to promote more substantive and inclusive recognition of customary forests. Thus, integrated legal reform is essential to achieving equitable and sustainable agrarian justice.